Azole resistance in Aspergillus isolates from animals or their direct environment (2013–2023): a systematic review - Dieste-Pérez, Lucía; Holstege, Manon M. C.; de Jong, Judith E.; Heuvelink, Annet E. (Frontiers in Veterinary Science, 2025)
The resistance of Aspergillus species to azoles in human medicine is gaining increasing attention, and the role of animals and agricultural practices in this issue is becoming a significant source of concern. To gain better insights into the occurrence of azole resistance in Aspergillus spp. isolates from animals, a systematic literature review was conducted. Searches were conducted in the PubMed and Scopus databases for articles addressing azole resistance in Aspergillus spp. isolates from both animals and their immediate environments, published between 2013 and 2024. Descriptive clinical cases were analyzed separately from articles providing in-vitro susceptibility test results. MIC50 and MIC90 values, along with the number of non-wild type (NWT) isolates, were either directly extracted from the articles or calculated based on published results of individual isolates or MIC distributions. Ultimately, seventy-three out of 2042 articles were included in the analysis. Articles reporting clinical cases included only horses, dogs, cats, zoo animals, and wildlife, with the majority of cases occurring outside Europe. Generally, successful clinical remission or recovery followed prolonged and continuous fungicide azole treatments, regardless of the azole-Aspergillus spp.-animal category combination. Itraconazole was the most frequently noted treatment in clinical cases involving companion animals (dogs and cats) and horses. The weighted geometric mean of the MIC50 values for itraconazole was lowest for A. fumigatus isolates within the companion animal category. Zoo animals and wildlife were often treated with voriconazole, and the weighted geometric mean of the MIC50 values for this and other azoles was equal to or slightly lower than those calculated for A. fumigatus isolates from other animal categories. NWT A. fumigatus isolates were reported in zoo animals and wildlife, horses, companion animals, and poultry for several azoles, occurring both in Europe and beyond, in healthy and sick animals. In conclusion, zoo animals and wildlife, horses, and poultry represent a more significant concern regarding the prevalence of A. fumigatus and A. flavus NWT isolates than other animal categories. Insufficient data prevented conclusions about the situation specifically in Europe, and therefore, more systematic and comparable data are required.